The State of the Art of Methodological Research on the Role of the Brand in Local Products (International Journal of Applied Research in Management and Economics, 2024)
The products of the territory play an important role in the economic life of a country. They provide the right framework for economic and social development at the local and national levels. In the Albanian literature, there are no in-depth studies regarding the methodology used to increase the value of the local brand, and as a result of not researching this factor, this study helps the brand with local indicators. The purpose of this study is to provide an overview of the methodology in general and the method used in the research on the role of the brand with indicators of origin in local products in Albania. Methodologies are suggested, which consist of the examination of all methodological approaches for the role of the brand with local indicators and the identification of the method for researching the case study. For the importance of branding agricultural and livestock products with local indicators and preserving their originality and development, the concept of the methodology and method that must be followed in order to give accurate results and the values that the local brand carries in itself in development is important of it and the area that is applied to increasing the economic performance of agro-processing industries. The literature shows that the impact of increasing the value of the territorial brand in our country is based on the case study method and the cross-case research methodology. Meanwhile, in order to prove the importance of the local brand in increasing the consumption of products and increasing the income of the industries in this sector, the STATA program was used to process the data collected from consumers, and the "R" program was used to process the data of the collected industries. From the results of the research, it has been established that the local brand affects the increase in consumption and income in the agricultural and livestock agro-processing industries. This paper serves as a methodology for studies in this field that are necessary for the case of Albania.